Enhanced amperometric detection of paracetamol by immobilized cobalt ion on functionalized MWCNTs - Chitosan thin film - Akhter, Shamima; Basirun, Wan Jefrey; Alias, Yatimah; Johan, Mohd Rafie; Bagheri, Samira; Shalauddin, Md; Ladan, Magaji; Anuar, Nadzirah Sofia (Elsevier, 2018)
In the present study, a nanocomposite of f-MWCNTs-chitosan-Co was prepared by the immobilization of Co(II) on f-MWCNTs-chitosan by a self-assembly method and used for the quantitative determination of paracetamol (PR). The composite was characterized by field emission scanning electron microscopy (FESEM) and energy dispersive x-ray analysis (EDX). The electroactivity of cobalt immobilized on f-MWCNTs-chitosan was assessed during the electro-oxidation of paracetamol. The prepared GCE modified f-MWCNTs/CTS-Co showed strong electrocatalytic activity towards the oxidation of PR. The electrochemical performances were investigated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and differential pulse voltammetry (DPV). Under favorable experimental conditions, differential pulse voltammetry showed a linear dynamic range between 0.1 and 400 μmol L−1 with a detection limit of 0.01 μmol L−1 for the PR solution. The fabricated sensor exhibited significant selectivity towards PR detection. The fabricated sensor was successfully applied for the determination of PR in commercial tablets and human serum sample.